Алелі гена Ppd-D1 у зразках колекції Aegilops tauschii і м’якої пшениці - Чеботар, Г.О.; Чеботар, С.В.; Бабенко, Д.О.; Моцний, І.І.; Щербань, А.Б.; Cивола, Ю.М. (Вiopolymers and Cell, 2012)
Light period significantly influences on the growth and development of plants. One of the major genes of photoperiod sensitivity is Ppd-D1, located on the chromosome 2D. The aim of the work was to determine the alleles and molecular structure of Ppd-D1 gene in samples from the collection of Ae. tauschii accessions, which have different flowering periods, and in 29 Ukrainian wheat varieties. Methods. We used methods of allele-specific PCR with primers to the Ppd-D1 gene, sequencing and Blast-analysis. Results. The collection of Ae. tauschii accessions and several varieties of winter and spring wheat was studied. The molecular structure of the allelic variants (414, 429 and 453 b. p.) of Ppd-D1b gene was determined in the collection of Aegilops. tauschii accessions. Conclusions. The Ppd-D1a allele was present in all studied varieties of winter wheat. 60 % of spring wheat is characterized by Ppd-D1b allele (size of amplification products 414 b. p.). Blast-analysis of the sequence data banks on the basis of the reference sequence of sample k-1322 from the collection of Ae. tauschii accessions has shown a high homology (80 to 100 %) between the nucleotide sequences of PRR genes, that characterize the A and D genomes of representatives of the genera Triticum and Aegilops. Keywords: Aegilops tauschii, bread wheat, allele-specific PCR, phd-D1.